exCTF simulator: Simulation tool for phase contrast transfer function for aberration-corrected transmission electron microscopy - Sang-Chul Lee; Jong-Man Jeung; Sang-Gil Lee; Jin-Gyu Kim (Journal of Analytical Science and Technology, 2020)
Abstract Background The contrast transfer function (CTF) is an important principle in the field of transmission electron microscopy (TEM) imaging. It provides information on how the electron wave that interacted with a sample (in frequency domain) in an objective lens is transferred to the imaging system (in real space domain) depending on the effects of lens aberrations. Based on the CTF calculation, various useful results, such as the TEM instrumental information limit and optimal imaging condition, can be estimated. Recently, aberration-corrected TEM (AC-TEM) has been widely applied in various research fields for imaging at the nanoscale or atomic scale. To use AC-TEM effectively, a deep understanding of the complicated CTF with an electron wave controlled via an aberration corrector is required. Unfortunately, this complicated CTF is difficult to understand for most microscopists without the use of computational tools. In this study, we develop the extended CTF (exCTF) simulator to perform the full as well as simple CTF calculation. Findings We successfully developed the exCTF simulator, which can obtain more information than previously reported software. The exCTF simulator not only calculates the CTF for basic optical information that can be obtained in conventional TEM, but also can calculate the extended CTF with various aberrations (up to fifth order) for more detailed information obtained in advanced high-performance AC-TEM in one-dimensional and two-dimensional formats. The user interface of the simulator includes CTF calculation, saving, and edit functions for five graphs for different conditions, allowing for detailed comparative analysis. Conclusion We confirmed that the exCTF simulator produced reliable calculation data for various applications. The exCTF simulator made it easy to obtain instrumental performance information and demonstrated the influence of optical aberrations on the actual resolution of AC-TEM. Consequently, the proposed exCTF simulator is expected to be useful to microscopists as a simulation tool for electron microscopy and as a training tool for electron optics.